2020
DOI: 10.1111/ajco.13437
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy service need in the Pacific Island countries

Abstract: Background: Pacific Island Countries and Territories (PICTs) have experienced an increase in cancer burden in the recent years. There is need for major investments in the cancer treatment facilities including radiotherapy (RT).Aims: This study aimed to provide a quantitative estimation of the effect of establishing new RT facilities on patient access through Geographic Information System (GIS) modelling of population density and service availability to assess the best location for a new RT centre when there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Twenty-four studies used GIS to describe geographic accessibility to RT (Table 3 ), measured via travel distance 5 , 34 - 49 and travel time 3 , 4 , 20 , 22 , 35 , 36 , 45 , 48 , 50 - 55 to nearest RT centers. These were calculated on the basis of travel by road, 3 , 4 , 20 , 22 , 34 - 36 , 38 , 40 , 42 - 57 air, 36 , 58 or by Euclidean distance. 5 , 37 , 39 , 41 Several studies calculated geographic catchment areas and defined vulnerable population groups to describe access.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-four studies used GIS to describe geographic accessibility to RT (Table 3 ), measured via travel distance 5 , 34 - 49 and travel time 3 , 4 , 20 , 22 , 35 , 36 , 45 , 48 , 50 - 55 to nearest RT centers. These were calculated on the basis of travel by road, 3 , 4 , 20 , 22 , 34 - 36 , 38 , 40 , 42 - 57 air, 36 , 58 or by Euclidean distance. 5 , 37 , 39 , 41 Several studies calculated geographic catchment areas and defined vulnerable population groups to describe access.…”
Section: Resultsmentioning
confidence: 99%
“… 39 In Italy, adding RT centers significantly reduced the proportion of patients with breast cancer who omit postoperative RT. 35 Shafiq et al 58 showed that establishing 26 new megavoltage machines in areas of highest need in Pacific Island Countries and Territories on the basis of 2040 modeled cancer incidence met 90% of the RT demands, compared with 14% with current resources. Aggarwal et al 71 found that 21% of patients with prostate cancer traveled beyond their nearest RT center for treatment in the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Local healthcare professionals need to be trained and provided with continuing professional support and education to ensure sustainability of services, which can often be threatened by the migration of skilled staff to wealthier countries. Provision of radiation treatment, in particular, is affected by all these challenges and none of the island communities described has a functioning radiotherapy service, although recent modeling 17 suggests that 29 megavoltage machines are needed to meet current demand in PICTs.…”
Section: Common Challengesmentioning
confidence: 99%